O rock e o sertão : juventude, consumo e estilo de vida na produção cultural sergipana - Oliveira, Tânia Carolina Viana de (2013)
Through the perspectives of cultural studies and studies of musical styles, identities, youth and cultural consumption, the present work aims to study a music festival called "Festival de Música Independente Rock Sertão", held in "Nossa Senhora da Glória" town, situated hinterland of Sergipe, 79 miles away from the capital. Organized by a young local group of cultural producers, had in 2012 its tenth edition. The objective is to analyze the production and consumption of a rock festival held in the hinterlands of Sergipe and organized by the local youth. I will demonstrate how this festival is programmed and how the rock is used by producers and consumers as a style marker. Seeking raise questions about the cultural production of a rock festival that takes place in region that spreads "forró" and "axé" as ideal music style. These styles are very different from rock and festival´s main theme.